Fate and health risks assessment of some pesticides residues during industrial rice processing in Argentina - Medina, María Belén (2021)
The residues of deltamethrin, penconazole, kresoxim-methyl, cyproconazole, epoxiconazole and azoxystrobin were determined in husk rice, brown rice, husk and bran, fifty samples of each matrix, obtained from industrial rice facilities, to estimate the distribution of contamination levels during industrial rice processing; and to estimate the exposure to these pesticides through rice intake. The analytical methodologies required were validated. QuEChERS extraction and gas chromatography-mass spectrometry were used. All methods showed good linearity (r2 > 0.9996), adequate recoveries (between 80.0–102.0%) and relative standard deviations lower than 9.9 %. A total of 250 samples were analyzed, finding that the polishing stage reached the greatest pesticide reduction. Considering the overall process, the initial concentration of pesticides in husk rice was reduced in the range of 66.1–74.7%. Process factors were lower than 0.69 and 0.36 for brown and polished rice, respectively. Estimated Dietary Intake were below 0.83 %, 2.34 % and 3.70 % of ADI, for men, women, and children, respectively. Hazard quotient was estimated, and it was lower than 1 in all cases, showing a low potential risk for human health in terms of residue ingestion.